2020
DOI: 10.1038/s41598-020-71740-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity enhancement in gold decorated graphene nanosheets in ethylene glycol based nanofluid

Abstract: We report on the synthesis and thermal conductivity of gold nanoparticles (AuNPs) decorated graphene nanosheets (GNs) based nanofluids. The GNs-AuNPs nanocomposites were synthesised using a nanosecond pulsed Nd:YAG laser (wavelength = 1,064 nm) to ablate graphite target followed by Au in ethylene glycol (EG) base fluid to obtain GNs-AuNPs/EG hybrid nanofluid. The characterization of the as-synthesised GNs-AuNPs/EG hybrid nanofluid confirmed a sheet-like structure of GNs decorated with crystalline AuNPs with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This reproducible thermal conductivity enhancement was reported varying from 7 to 18% relatively to that of the host medium of C 2 H 6 O 2 or H 2 O. Recently, Mbambo et al reported an enhancement of about 33% in a multi-components nanosystem of Ag or Au grafted Graphene/C 2 H 6 O 2 based nanofluids 16 , 17 .…”
Section: Introductionmentioning
confidence: 70%
“…This reproducible thermal conductivity enhancement was reported varying from 7 to 18% relatively to that of the host medium of C 2 H 6 O 2 or H 2 O. Recently, Mbambo et al reported an enhancement of about 33% in a multi-components nanosystem of Ag or Au grafted Graphene/C 2 H 6 O 2 based nanofluids 16 , 17 .…”
Section: Introductionmentioning
confidence: 70%
“…The experimental data related to this hybrid nanofluid indicated 27% and 45% enhancements in thermal conductivity at high temperatures with EG base fluid and deionized (DI) water. 49 In another study, GNs–Au NPs hybrid nanofluid was synthesized by Mbambo 50 in ethylene glycol and the thermal conductivity was enhanced up to 26% in the range of 25–45 °C. Thus, Au (301 W m −1 K −1 ) and GO (2000–5000 W m −1 K −1 ) NPs with varying thermal conductivities were able to generate considerable thermal properties through addition to the water base fluids.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated the potential for useful applications in heat transfer systems by emphasizing the notable increases in thermal conductivity obtained by adding these nanoplatelets to the fluid. Mbambo et al [15] investigated the increase in thermal conductivity in nanofluids that contained graphene nanosheets coated with gold and distributed in ethylene glycol. They provided details on the mechanics behind the increased thermal conductivity and offered suggestions for possible uses of these nanofluids in energy and thermal management systems.…”
Section: Introductionmentioning
confidence: 99%